Perceived barriers, facilitators and usefulness of a psychoeducational intervention for individuals with chronic musculoskeletal pain and depression in primary care - Tomé-Pires, Catarina; Aragonès, Enric; Rambla, Concepción; López-Cortacans, Germán; Sánchez-Rodríguez, Elisabet; Caballero, Antonia; Miró, Jordi (Frontiers in Psychology, 2023)
Background and aims: Self-management interventions have the potential to improve patient’ pain condition as they involve tasks aimed at managing symptoms and reducing interference with activities, mood and relationships due to pain. However, research on factors that facilitate or hinder pain self-management has overlooked patients with both chronic musculoskeletal pain and depression in primary care settings, also leaving unattended patient views on the usefulness of such programs. Thus, the main aim of this study was to gather meaningful information to help promoting adequate self-management. Specifically, it attempts to identify patients’ perceptions of barriers and facilitators of group-based psychoeducational intervention and to explore its perceived usefulness in promoting self-management. Method: This qualitative study explored perceived barriers and facilitators of a psychoeducational intervention for the management of chronic musculoskeletal pain and depression previously tested in a Randomized Control Trial. We conducted focus groups and individual interviews with fifteen adult patients with both chronic musculoskeletal pain and depression recruited from primary care centres in Tarragona province (Catalonia, Spain). A content thematic analysis was carried out to examine the data. This study followed the Consolidated Criteria for Reporting Qualitative Research (COREQ) guidelines. Results: Findings revealed that perceived barriers included lack of motivation, time constraints, pain, depression, ineffectiveness of pain-relief strategies and activity avoidance. Facilitators were having a supportive family/friends, the positive effects of self-management, high motivation, being a proactive patient. Peer support and identification, the positive effect of sessions, and free expression were highlighted as key elements of the psychoeducational intervention. Conclusions: The psychoeducational intervention was perceived as useful in promoting self-management practices. Barriers and facilitators in using self-management strategies were related, mainly, to internal personal characteristics of the patients being similar among different cultural backgrounds and distinct chronic conditions. Implications: These findings can help to guide clinicians in the development and implementation of more effective pain self-management interventions for patients with chronic pain and depression by attending to their needs and preferences